PENGARUH PENAMBAHAN DEKSTRIN TERHADAP MUTU KOPI BLOK - Chasri Nurhayati (Balai Riset dan Standardisasi Industri Palembang, 2010)
Research about the effects of dextrin addition on the quality of coffee cube has been conducted. This research aims to know the effects of dextrin on the quality of block coffee. Full random design is used with ten treatments consisting of D0 (control) without dextrin, D1(0.5% dextrin), D2(1%), D3(1.5%), D4(2%), D5(2.5%), D6(3%), D7(3.5%), D8(4%), D9(4.5%),D10(5%), all treatments are repeated three times. The observed parameters include pH of the prepared coffee, moisture content, extra content, hardness of coffee and organoleptic test of prepared coffee taste. The result of this research shows that the treatment has significant effect on moisture content, extra content, pH of the prepared coffee, the solubility, hardness and taste of coffee. Characteristics of block coffee with 0-3% dextrin addition produce moisture content in range of 6.31% to 6.60%, extract content in range of 29.41% to 59.72%, pH of prepared coffee in range 5.62% to 5.806%, solubility in range of 43.80% to 60.1%, and hardness of coffee in range of 0.21% to 0.59%. For organoleptic test on the taste of prepared coffee in treatments of D0 to D6, there is no significant effect on the taste of coffee while for treatments of D7 to D9 have significant effect. Dextrin addition under 3% does not have effect on the taste of coffee but dextrin addition above 3% will affect the taste of coffee.